Optimization Of Heavy Forces For Humanitarian Missions And Emergency Response - Susetyo, Eko; S, Guntur; Andreas N, Djoko; Harefa, Faonaso (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
Climate change increases the frequency of disasters, while access to remote areas remains a challenge. In military operations other than war (OMSP), the Army played a role in disaster management. High-mobility troops can be optimized for evacuation, distribution of assistance, and emergency responses that are faster and more effective. Previous research discussed more the role of cavalry in military aspects and state events, while the study of cavalry optimization in non-war operations, especially humanitarian missions and disaster response, is still limited. To fill this gap, this research evaluates the effectiveness of the horsemen in emergency response operations in areas difficult to access. This study uses the Mixed Methods Explanatory Sequential Design approach, qualitative analysis with NVIVO 12, and quantitative uses SEM-PLS 4. NVIVO 12 analysis revealed that the main factors in optimizing horse troops include increasing mobility, accessibility, coordination between agencies, and modernization of equipment and training. SEM-PLS 4 results show that cavalcaded troops have a significant influence on evacuation, distribution of aid, and emergency response that is faster and more effective with the coefficient of pathway 0.529 (T-statistics 3.932; P-value 0.000). This study recommends the integration of cavalry troops, especially cavalry in the national disaster response policy, but the importance of improving infrastructure, modernization of equipment, and special training to increase operational effectiveness.